2017
DOI: 10.1021/jacs.6b12541
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of mycobacterial membrane dynamics in live cells

Abstract: Mycobacteria are endowed with a highly impermeable mycomembrane that confers intrinsic resistance to many antibiotics. Several unique mycomembrane glycolipids have been isolated and structurally characterized, but the underlying organization and dynamics of glycolipids within the cell envelope remain poorly understood. We report here a study of mycomembrane dynamics that was enabled by trehalose–fluorophore conjugates capable of labeling trehalose glycolipids in live actinomycetes. We identified fluorescein–tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 50 publications
8
127
0
Order By: Relevance
“…B) Structures of trehalose, TMM and TDM and their interconversion by Ag85. C) 6‐FITC‐Tre . D) DMN‐Tre .…”
Section: Chemical Reporters For Microbiologymentioning
confidence: 99%
“…B) Structures of trehalose, TMM and TDM and their interconversion by Ag85. C) 6‐FITC‐Tre . D) DMN‐Tre .…”
Section: Chemical Reporters For Microbiologymentioning
confidence: 99%
“…M. tuberculosis is surrounded by a characteristically thick and waxy cell envelope containing interconnected polymers of mycolic acids (MAs), arabinogalactan (AG) and peptidoglycan (PG) (17,18). This unique envelope renders M. tuberculosis hydrophobic; a trait primarily attributed to the presence of the MAs which are long chain fatty acids of up to 90 carbon atoms in length (19).…”
Section: The Mycobacteriology Of M Tuberculosismentioning
confidence: 99%
“…This unique envelope renders M. tuberculosis hydrophobic; a trait primarily attributed to the presence of the MAs which are long chain fatty acids of up to 90 carbon atoms in length (19). The hydrophobic membrane acts as a permeability barrier towards various hydrophilic and lipophilic compounds making M. tuberculosis inherently resistant to antibiotics (17,18,20,21). However, the inherent resistance cannot solely be attributed to the impermeable membrane since experiments have shown that drugs are able reach cytotoxic levels within cells (20).…”
Section: The Mycobacteriology Of M Tuberculosismentioning
confidence: 99%
“…FRAP measurements by Edidin’s group using class I MHC molecules revealed that mutants with reduced N-linked glycans have increased lateral diffusion as compared with wild-type and that a large mobile fraction of diffusing glycoproteins enabled bleached regions to become repopulated with fluorescent molecules [24]. In contrast to these pioneering studies, contemporary FRAP imaging of the dynamics of glycolipids within the cell envelope of mycobacterial membranes exploits the power of metabolically incorporated analogues [26]. …”
Section: Imaging An Ensemble Of Glycans In Live Cellsmentioning
confidence: 99%